Multidisciplinary development of a simulation of industrial plant disasters designed for improving safety through training and new procedures. (16th July 2019) - Frascio, Marco; Cortese, Katia; Sinelshchikov, Kirill; Longo, Francesco
Industrial accidents are an unfortunate reality, therefore there are just a limited number of situational training exercises to cope with the management of these kinds of emergencies. The authors propose a simulation approach for developing innovative response procedures during industrial crises integrated with start system triage model. The proposed simulator is based on an interoperable architecture using the new MS2G paradigm and it designed for being federated by IEEE 1516 HLA with other systems. The paper presents its use as test-bed on a specific case study conducting experiments over the SPIDER virtual platform developed by simulation team. In facts these experiments were based on two university classes that performed tests and training experiences on multiple target functions including mission time, detection, classification and securing of injured people. The analysis included also use of innovative procedures based on autonomous systems. The obtained results highlighted improvements on the learning curves with respect to specific target functions. These results confirm the potential of this approach as a training strategy that combines medical skills with engineering to improve reaction capabilities and situation awareness during industrial crises.